Ultrasonographic Evaluation of Foetal Binocular Distance in Second & Third Trimester of Pregnancy and Correlation with Gestation Age - Islam, Md. Menhazul; Akter, Taslima; Mohammad, Abu Sayeed; Islam, Saiful; Alam, Farzana; Goswami, Uday; Al-Azad, Salah Uddin; Selim, Shahjada (Journal of Current and Advance Medical Research, 2016)
Background: Foetal Binocular Distance in Second & Third Trimester of Pregnancy and correlation with Gestation Age is important. Objective: The purpose of the study was to sonographically measure the foetal binocular distance, determine the foetal gestational age & to find out relationship between them in 2nd & 3rd trimester of gestation. Methodology: This cross sectional study was carried out in the department of radiology and imaging Mymensingh Medical College Hospital, Mymensingh and Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh during the period of July 2012 to June 2013. In all the cases BPD, FL, AC, Binocular distance (BD) in cm and gestational age in weeks were measured by USG. Each patient was voluntary enrolled into the study without any specific indication. The measurement was performed only once for each patient. The foetal outer binocular distance was identified in the occipito-transverse or occipito-posterior-foetal positions. With the head in the occipito-posterior position, the transducer was placed in a plane that transected the occiput, orbits, and nasal processes. Measurements were obtained only when the fetal face was directly perpendicular to the uterine wall, since measurements in an oblique plane were considered to be unreliable. Result: The correlation between binocular distance (BD) in cm and gestational age (GA) in wks was calculated. This correlation was highly significant (r = 0. 973; p<0.001).Conclusion:Excellent correlation was found to exist between binocular diameter and gestational age. In the absence of known date of last menstrual period or where fundal height does not agree with dates, these parameters are valuable in estimating the gestational age of the foetus. Journal of Current and Advance Medical Research, 2016;3(1):10-15